2017
DOI: 10.1007/s13300-017-0303-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vildagliptin Add-on Insulin Therapy on Nocturnal Glycemic Variations in Uncontrolled Type 2 Diabetes

Abstract: IntroductionTo investigate whether vildagliptin add-on insulin therapy improves glycemic variations in patients with uncontrolled type 2 diabetes (T2D) compared to patients with placebo therapy.MethodsThis was a 24-week, single-center, double-blind, placebo-controlled trial. Inadequately controlled T2D patients treated with insulin therapy were recruited between June 2012 and April 2013. The trial included a 2-week screening period and a 24-week randomized period. Subjects were randomly assigned to a vildaglip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…All patients were subjected to 4-day retrospective CGM (Sof-sensor, CGMS-Gold, Medtronic Incorp., Northridge, CA, USA) at the last 4 days in this study [ 18 , 23 ]. All subjects were instructed to maintain moderate physical activity and received breakfast (0700), lunch (1100) and dinner (1700).…”
Section: Methodsmentioning
confidence: 99%
“…All patients were subjected to 4-day retrospective CGM (Sof-sensor, CGMS-Gold, Medtronic Incorp., Northridge, CA, USA) at the last 4 days in this study [ 18 , 23 ]. All subjects were instructed to maintain moderate physical activity and received breakfast (0700), lunch (1100) and dinner (1700).…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes is responsible for reducing blood levels of albumin, which is also indicative of liver failure. Vildagliptin add-on insulin therapy in T2DM also did not alter the level of liver enzymes 32 , whereas in a hepatic fibrosis model the administration of Quercetin resulted in maintenance of ALT/AST levels and increased serum albumin levels, suggesting a possible hepatoprotective effect 39 . Diabetes is characterized by redox imbalance in the kidneys that can lead to nephropathy 40 .…”
Section: Discussionmentioning
confidence: 89%
“…Atherosclerosis is a pathological condition resulting from lipid deposition and atheromatous plaque formation in the subendothelial layer of blood vessels, and oxidative stress and inflammatory responses are among the major triggers 31 . A study with patients with uncontrolled T2DM showed that Vildagliptin as an add-on to insulin therapy did not alter the lipid profile 32 , while Vildagliptin treatment ameliorated this parameter in diabetic mice 33 . The QV formulation had a beneficial effect in reducing atherogenic cholesterol fractions (decrease in non-HDL fraction accompanied by increase HDL fraction), while daily administration of insulin was responsible for increasing triacylglycerol levels when compared to treatment with the QV formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the structured seven-point self-monitoring of blood glucose, CGMS can monitor the subcutaneous interstitial fluid glucose level automatically every 5 min and thus provide dynamic changes of blood glucose for no less than 72 h to show more comprehensively and accurately the blood glucose excursion throughout the day. Hence, the CGMS is a reliable and useful tool to measure the GV of patients with diabetes mellitus [ 23 , 24 ]. In the present study, we used CGMS to compare the efficacy, safety, risk of hypoglycemia, and glucose excursion profile of two low premixed insulin lispro 25s, Prandilin 25 and Humalog mix 25, in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%